Analisis Pengaruh Loan to Deposit Ratio (LDR) dan Net Interest Margin (NIM) Terhadap Return on Assets (ROA) pada PT Bank Rakyat Indonesia (Persero) Tbk Periode 2018-2025 - Jihan Hafidzah; Denny Hambali (CV. Ulil Albab Corp, 2026)
Profitability stability is a crucial indicator in assessing the financial resilience of the banking sector against economic dynamics. This study aims to analyze the contribution of the Loan to Deposit Ratio (LDR) and Net Interest Margin (NIM) toward Return on Assets (ROA) at PT Bank Rakyat Indonesia (Persero) Tbk for the 2018-2025 period. Using a quantitative methodology and multiple linear regression analysis on 32 quarterly data samples, this study dissects the relationships between variables through classical assumption tests and hypothesis testing. The research findings indicate that, simultaneously, LDR and NIM exert a significant influence on ROA. Partially, NIM was found to be the most dominant determinant in influencing bank profitability, with a t-statistic of 7.062. This suggests that optimizing net interest income and maintaining efficiency in liquidity management are key to sustaining asset performance. This study recommends strengthening credit risk management and adaptive intermediation strategies to ensure sustainable earnings growth in the future.